Pengaruh Budaya Kaizen terhadap Kinerja Karyawan pada PT. JNE Station Center Gedebage Bandung - Azra Putriyadira Tanjung; Suwarsi, Sri; Wirayudha, Aditia (UNISBA Press, 2024)
Abstract. Performance is the result or achievement that has been achieved by employees for the tasks and responsibilities given. Many factors can improve performance, one of which is organizational culture. The organizational culture applied by PT. JNE Station Center Gedebage Bandung, namely Kaizen Culture. Kaizen culture is an organizational culture derived from Japanese culture, namely